A companion to the "Indian mutiny" of 1857 - Taylor, P. J. O. (New York : Oxford University Press, 1996)
Encyclopedia of the 1857-1858, Indian freedom movement.
Includes bibliographical references.
Keywords: India -- History -- Sepoy Rebellion, 1857-1858 -- Encyclopedias; 61-92